An Aerial–Aquatic Hitchhiking Robot with Remora‐Inspired Tactile Sensors and Thrust Vectoring Units - Lei Li; Wenbo Liu; Bocheng Tian; Peiyu Hu; Wenzhuo Gao; Yuchen Liu; Fuqiang Yang; Youning Duo; Hongru Cai; Yiyuan Zhang; Zhouhao Zhang; Zimo Li; et al. (Advanced Intelligent Systems, 2025)
Hybrid aerial–aquatic robots can operate in both air and water and cross between these two. They can be applied to amphibious observation, maritime search and rescue, and cross‐domain environmental monitoring. Herein, an aerial–aquatic hitchhiking robot is proposed that can fly, swim, and rapidly cross the air–water boundaries (0.16 s) and autonomously attach to surfaces in both air and water. Inspired by the mechanoreceptors of the remora (Echeneis naucrates) disc, the robot's hitchhiking device is equipped with two flexible bioinspired tactile sensors (FBTS) based on a triboelectric nanogenerator for tactile sensing of attachment status. Based on tactile sensing, the robot can perform reattachment after leakage or adhesion failure, enabling it to achieve long‐term adhesion on complex surfaces. The rotor‐based aerial–aquatic robot, which has two thrust vectoring units for underwater locomotion, can maneuver to pitch, yaw, and roll 360° and control precision motion position. The field tests show that the robot can continuously cross the air–water boundary, attach to the rough stone surface, and record video in both air and underwater. This study may shed light on future autonomous robots capable of intelligent navigation, adhesion, and operation in complex aerial–aquatic environments.